Arabidopsis AAR2, a conserved splicing factor in eukaryotes, acts in microRNA biogenesis - Fan, Lusheng (2022)
MicroRNAs (miRNAs) play an essential role in plant growth and development, and as such, their biogenesis is fine-tuned via regulation of the core microprocessor components. Here, we report that Arabidopsis AAR2, a homolog of a U5 snRNP assembly factor in yeast and humans, not only acts in splicing but also promotes miRNA biogenesis. AAR2 interacts with the microprocessor component hyponastic leaves 1 (HYL1) in the cytoplasm, nucleus, and dicing bodies. In aar2 mutants, abundance of nonphosphorylated HYL1, the active form of HYL1, and the number of HYL1-labeled dicing bodies are reduced. Primary miRNA (pri-miRNA) accumulation is compromised despite normal promoter activities of MIR genes in aar2 mutants. RNA decay assays show that the aar2-1 mutation leads to faster degradation of pri-miRNAs in a HYL1-dependent manner, which reveals a previously unknown and negative role of HYL1 in miRNA biogenesis. Taken together, our findings reveal a dual role of AAR2 in miRNA biogenesis and pre-messenger RNA splicing.